Collaborative Governance in Blue Economy Policy in the Development of Marine Tourism In Makassar City - Muhammad Roem, Muhammad Akmal Ibrahim, Nurdin Nara, Muhammad Tang Abdullah, Didik Iskandar (South Eastern European Journal of Public Health, 2025)
In developing marine tourism, efforts are made to consider environmental preservation and natural conditions, also known as the blue economy, so the collaboration of all stakeholders is needed to realize it. This study aims to analyze collaborative governance in blue economy policy on marine tourism development in Makassar City. This study uses a qualitative research approach with data collection methods, namely observation, in-depth interviews, and documentation. Informants are parties who are authorized and directly involved in the management of marine tourism development in Makassar City. Data sources consist of primary and secondary data. The data analysis technique used is an interactive analysis model. The results of the study indicate that there has been collaborative action in the development of marine tourism in Makassar City using the Penta helix model, namely the involvement of the media and press, academics and students, the private sector, the community, and the government, both the provincial government and the city government. However, there is no special and specific legal umbrella related to the blue economy policy. In addition, the government's authority in the maritime sector still overlaps so that collaborative governance in the blue economy The policy on the development of marine tourism in Makassar City can be said to be still not optimal.